2007
DOI: 10.1074/jbc.m607712200
|View full text |Cite
|
Sign up to set email alerts
|

The MicroRNA let-7a Modulates Interleukin-6-dependent STAT-3 Survival Signaling in Malignant Human Cholangiocytes

Abstract: The inflammation-associated cytokine interleukin-6 (IL-6) can contribute to tumor growth and resistance to therapy by the activation of survival mechanisms. In several human cancers, IL-6-activated survival signaling involves the signal transducers and activators of transcription (Stat) factors or protein kinase cascades. microRNAs (miRNAs) are endogenous regulators of gene expression that are altered in expression in many cancers. However, the effect of inflammatory cytokines on miRNA expression and the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
126
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(132 citation statements)
references
References 31 publications
5
126
0
1
Order By: Relevance
“…Sustained cell proliferation in a micro-environment rich in inflammatory cells, cytokines/chemokines, growth factors and DNA-damaging agents (such as reactive oxygen and nitrogen species because of long-term inflammation) will lead to permanent genetic alterations and subsequent neoplastic transformation of the proliferating cells (Komori et al, 2008). For example, interleukin-6, an inflammatory cytokine, promotes human cholangiocarcinoma cells grown in vivo by inhibiting apoptosis through the activation of miRNAs including miR let-7a and miR370, thereby modulating the activation of STAT-3 pathways (Meng et al, 2007(Meng et al, , 2008Smirnova et al, 2007). It has also been shown that the sustained upregulation of the transcription factor nuclear factor kappaB (NF-kB) in the liver cells, through the paracrine action of tumour necrosis factor-a secreted from the neighbouring endothelia and inflammatory cells, may lead to the tumour development (Maeda et al, 2005;Choi et al, 2006;Sakurai et al, 2006;Luedde et al, 2007), given the activation of mitogenic and anti-apoptotic genes through NF-kB pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Sustained cell proliferation in a micro-environment rich in inflammatory cells, cytokines/chemokines, growth factors and DNA-damaging agents (such as reactive oxygen and nitrogen species because of long-term inflammation) will lead to permanent genetic alterations and subsequent neoplastic transformation of the proliferating cells (Komori et al, 2008). For example, interleukin-6, an inflammatory cytokine, promotes human cholangiocarcinoma cells grown in vivo by inhibiting apoptosis through the activation of miRNAs including miR let-7a and miR370, thereby modulating the activation of STAT-3 pathways (Meng et al, 2007(Meng et al, , 2008Smirnova et al, 2007). It has also been shown that the sustained upregulation of the transcription factor nuclear factor kappaB (NF-kB) in the liver cells, through the paracrine action of tumour necrosis factor-a secreted from the neighbouring endothelia and inflammatory cells, may lead to the tumour development (Maeda et al, 2005;Choi et al, 2006;Sakurai et al, 2006;Luedde et al, 2007), given the activation of mitogenic and anti-apoptotic genes through NF-kB pathways.…”
Section: Discussionmentioning
confidence: 99%
“…There are also reports that suggest an oncogenic function for let-7. 40,41 Thus, it is conceivable that let-7 may have pleiotropic cell-type specific biological effects depending on the milieu of expressed genes inside the cells. In DLBCL, abnormal down-regulation of the tumor suppressor PRDM1 due to an overexpressed let-7 may represent one of the mechanisms by which the latter promotes lymphomagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a new member of transcription factor STAT3, has been identified to play a dual role in PTEN loss-and EGFRvIII-induced gliomas with AKT activation (17). STAT3 has proved to be connected with the function of certain miRNAs that play a functional role in oncogenesis (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%